The International Plant Diagnostic Network (IPDN) in Africa: improving capacity for diagnosing diseases of banana (Musa spp.) and other African crops - Beed, Fenton D.; Miller, S.A.; Momol, M.T.; Gilbertson, R.; Kinyua, Z.M.; Xin, J.; García, L.; Harmon, C.L.; Vergot, P. (International Society for Horticultural Science, 2010)
Bananas (Musa spp.) are subject to a number of diseases that are difficult todiagnose early in development when control measures are most likely to besuccessful. Rapidly spreading new diseases, such as Xanthomonas wilt presentunique diagnostic challenges. Surveys conducted in East and West Africadocumented the lack of sufficient equipment, supplies, reference materials andtraining in the majority of plant pathology laboratories charged with diseasediagnoses. To begin to address these issues, the International Plant DiagnosticNetwork (IPDN) was established in East and West Africa in 2006, through theIntegrated Pest Management Collaborative Research Support Program (IPMCRSP). The IPDN is a diagnostic, communication and data network, modeled inpart on the United States National Plant Diagnostic Network. Software for digitalimaging and diagnosis and information management provides a platform forenhanced diagnosis and communication amongst clinicians and their clientele.Improved diagnostics tools and protocols were also developed and tested, including aPCR assay for Xanthomonas wilt. Training programs were conducted in Benin in2006, Kenya and the United States of America in 2007, and Uganda and Mali in2008, to enhance technical capacity amongst diagnosticians in East and West Africa.Initiatives such as IPDN can benefit by collaboration with other similar internetbasedinitiatives in Africa. One such activity is the East Africa PhytosanitaryInformation Committee (EAPIC). EAPIC is linked to the Food and AgriculturalOrganization’s International Plant Portal to provide the official national plantprotection organization posting of plant pests for each respective country, whichnow includes Kenya, Tanzania, Uganda and Zambia. The plant pest list will serve asa foundation from which to develop harmonized border inspection protocols, whichin turn support capacity building efforts in plant pest survey, identification and communication systems, such as IPDN.